Effectiveness of Instrumental Music Playback on Work Fatigue, WorkMorale, and Work Productivity Among Administrative Staff of PT. X - Fadly Hamzairi; Iwan muhammad Ramdan; Muhammad Sultan (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Work fatigue is a significant occupational health issue leading to decreased work capacity and an increased risk of workplace accidents, as evidenced by global and national data (ILO, BPJS Ketenagakerjaan). Administrative staff at PT. X experience demanding conditions, including monotonous tasks, long working hours (>10 hours), work overload, and deadline pressure, contributing to stress and fatigue. Creating a comfortable and pleasant work environment is one strategy to mitigate fatigue, with music intervention being a promising, non-invasive method. Previous studies suggest that music can reduce stress, improve mood, and enhance concentration. Objective : This study aimed to analyze the effectiveness of instrumental music playback in reducing work fatigue and increasing work morale and work productivity among administrative staff at PT. X. Design: A quantitative quasi-experimental study with a Two-Group Pretest-Posttest design. 40 administrative staff members were divided into an experimental group (n=20) and a control group (n=20). The experimental group was exposed to instrumental music played via speakers for 7 consecutive working days. The control group continued working without music. Data on work fatigue, work morale, and work productivity were collected using standardized questionnaires (KAUPK2 for fatigue, plus specific questionnaires for morale and productivity) before (pretest) and after (posttest) the intervention. The paired sample t-test was used to analyze work productivity data, and the Wilcoxon signed-rank test was used for work fatigue and morale data, with a significance level of α = 0.05. Results : The study found statistically significant differences in the experimental group after the music intervention: Work Fatigue: A significant reduction was observed (p-value < 0.001). The percentage of staff in the "light fatigue" category decreased from 65% to 10%, while those in the "normal" category increased from 35% to 90%. Work Morale: A significant improvement was recorded (p-value < 0.001). Staff with "good" morale increased from 50% to 95%. Work Productivity: A significant increase was confirmed (p-value < 0.001). Staff with "good" productivity rose from 35% to 85%. In contrast, the control group showed no improvement or a slight decline in these metrics. Conclusion/Lesson Learned : The study concludes that the playback of instrumental music is an effective intervention for significantly reducing work fatigue and enhancing both work morale and work productivity among administrative staff. It is recommended that companies consider implementing scheduled instrumental music sessions to create a more comfortable workenvironment, which can improve employees' mental well-being and overall organizationalperformance.